2019
DOI: 10.1002/acr2.1030
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematosus Is Associated With a High Risk of Venous Thromboembolism in Hospitalized Patients Leading to Poor Outcomes and a Higher Cost: Results From Nationwide Inpatient Sample Database 2003‐2011

Abstract: ObjectiveVenous thromboembolism (VTE) is a major cause of mortality and morbidity in hospitalized patients, particularly those with autoimmune disorders. The Nationwide Inpatient Sample (NIS) database was analyzed to determine trends in the rate of hospitalization, mortality from VTE, epidemiology, and outcomes in hospitalized patients with systemic lupus erythematosus (SLE) to assess its impact.MethodsThe 2003‐2011 NIS database of the Healthcare Cost and Utilization Project was queried to identify all adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…To clarify morbidity and mortality of patients with SLE on a national level, we completed a comprehensive review of SLE hospitalizations using the most recent release of the NIS database. Prior studies of the NIS either queried for specific diagnoses of interest, examined only the most frequent diagnoses seen in patients with SLE, or limited the diagnoses reviewed (3,4,7,10‐12,15). For example, a recent analysis by Dhital et al (10) of the NIS 2016 reported on several organ/disease categories, but unfortunately many of these categories were incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify morbidity and mortality of patients with SLE on a national level, we completed a comprehensive review of SLE hospitalizations using the most recent release of the NIS database. Prior studies of the NIS either queried for specific diagnoses of interest, examined only the most frequent diagnoses seen in patients with SLE, or limited the diagnoses reviewed (3,4,7,10‐12,15). For example, a recent analysis by Dhital et al (10) of the NIS 2016 reported on several organ/disease categories, but unfortunately many of these categories were incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, SLE patients have been described to have a higher risk of thrombotic complications, which cannot be sufficiently explained by traditional risk factors ( 44 , 45 ). Those thrombotic complications include platelet hyperfunction ( 46 ), thrombotic microangiopathies (TMA) ( 47 ), venous thromboembolism (VTE) ( 48 ) and atherosclerosis ( 49 ). Moreover, it has been shown that C1q and other complement components are deposited on platelets of SLE patients and are associated with venous as well as arterial thrombotic events in those patients ( 50 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, insights regarding the cost burden in the IMD population have been limited. Previously, cost studies of TE have focused on specific subtypes of TE, IMDs, or the cost burden of TEs among the general population or in populations without IMDs [7,[12][13][14]. For example, a retrospective study published in 2019 based on data from 2003 to 2011 found that hospitalization costs among patients with systemic lupus erythematosus who experienced VTEs were greater by $25,400 compared with those who did not experience VTEs [7].…”
Section: Discussionmentioning
confidence: 99%
“…TEs carry a significant economic burden [5]. Conservative estimates of the costs of incident venous TE (VTE) to the United States (US) healthcare system are approximately $7-10 billion each year [7]. TEs are also a strong predictor for unplanned readmissions in the US which can have a substantial economic impact on society [8].…”
Section: Introductionmentioning
confidence: 99%